Posted by **kate** on Sunday, November 18, 2007 at 11:39am.

can someone tell me if i did the problem correct (solve by completing the square) 4x^2+2x-3=0

x^2+(1/2)=3/4

x^2+(1/2)+(1/4)^2=3/4+(1/4)^2

(x+1/4)^2=13/16

x+1/4=+-sqrt 13/16

x+1/4=+-sqrt 13/4

x=-1/4+-sqrt 13/4

x=-1+-sqrt 13/4

## Answer This Question

## Related Questions

- Math Help please!! - Could someone show me how to solve these problems step by ...
- math,help,algebra I - I need help can someone help me get unstuck and let me ...
- math,algebra,help - Directions are simplify by combining like terms. x radiacal ...
- Math - How do you find a square root of a number that's not a perfect square? I'...
- Math(Roots) - sqrt(24) *I don't really get this stuff.Can somebody please help ...
- algebra - simplify: square root of 5 + square root of 20 - square root of 27 + ...
- math calculus please help! - l = lim as x approaches 0 of x/(the square root of...
- Algebra - Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(...
- Inequality - When I solve the inquality 2x^2 - 6 < 0, I get x < + or - ...
- Surds - Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed ...

More Related Questions